FINDING PREPOSITION IN Q.S AL-KAHF - Sinaga, Yusni (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Looking at the limited time for people, especially for students and looking at so many subjects that must be studied by a student, it seems that students do not have time to study their religious. Meanwhile, references to the teachings of the good character it self are only found in the students’ religious scriptures. so a wise teacher must be abble to involve the holy kitab of each student in every material being taught such as Al- Qur’an for Moeslem students’. Because all references can be found in the Al- Qur;an, for instance in surah Al-Kahfi specifically for the language mathery preposition. Al Qur’an can be used as a media for exercises and also as a media for finding examples of the preposition in grammar matery.